THE ROLE OF GROUP 3 INNATE LYMPHOID CELLS (ILC3) IN GM-CSF/CSF2RB-DEPENDENT INTESTINAL HOMEOSTASIS IN CROHN'S DISEASE. (22nd January 2022) - Chuang, Ling-shiang; Morrison, Joshua; Chai, Zhi; Korie, Ujunwa; Mortha, Arthur; Gnjatic, Sacha; Cho, Judy
Abstract: Inflammatory Bowel Disease (IBD) is comprised of two subtypes, Crohn's disease (CD) and ulcerative colitis (UC). Genome-wide association studies (GWAS) of IBD identified 240 loci significantly associated with IBD risk. CSF2RB, one of the identified IBD-associated genes and the receptor for GM-CSF signaling, is responsible for maintaining intestinal homeostasis through retinoic acid (RA) production by macrophages and dendritic cells. GM-CSF (Sargramostim) treatment showed a promising result for preventing intestinal injury and inflammation in both a murine and our novel zebrafish model. However, due to GM-CSF-neutralizing antibodies present in patients, Sargramostim failed in a large cohort Phase II clinical trial. This GM-CSF-dependent homeostasis relies on the balance of innate lymphoid cells (ILCs). In human patients, we report that during inflammation in CD, there is a decrease of NCR+ ILC3s while proinflammatory ILC1s rapidly increase. Neutralizing GM-CSF auto-antibodies were detected in the pre-disease stage (ILC1 low & ILC3 low) in CD patients, a different result from CSF2RB frameshift allele carriers (ILC1 low & ILC3 high) (Figure 1). We developed a novel zebrafish model to mimic the acute and chronic nature of IBD disease pathogenicity in vivo . In our model, human GM-CSF treatment significantly alleviated intestinal injury but showed no effect during mucosal healing. With a CRISPR knockout csf2rb zebrafish line, we showed this protective effect is CSF2RB-dependent. Using single-cell technologies, DSS-induced injury increases rorc + ILC3s. These ILC3 cell proportion changes were diminished in csf2rb -/- zebrafish (Figure 2). Figure 1. Distinct ILC subpopulations between anti-GM-CSF antibodies and CSFRB mutation carriers. Scatter plot of the PC1 values of the ILC3 gene list (ILC3-PC) (y axis) against the PC1 values of the ILC1 gene list (ILC1-PC) (x axis). Both ILC1-PC and ILC3-PC were derived from PCA analysis of signature gene lists of ILC1 and ILC3 cell types against a sub-dataset of the bulk mRNAseq samples from the MSCCR. Red dot indicate patient with anti-GM-CSF antibody. The logarithm antibody titer was shown with the intensity of red color. The green dots indicate the CSF2RB heterozygote carriers. Figure 2. GM-CSF protects against DSS-induced intestinal injury and regulates ILC3. (A-B) Treatment of human GM-CSF significantly reduces intestinal injury in dose-dependent manner in WT (A) but not CSF2RB-/- (B). ***, P< 0.001 (C) Analyzing scRNAseq data of zebrafish intestine cells, RORC + (ILC3) cell proportion over total immune cells increases with DSS injury and decreases with human GM-CSF co-treatment. There is no RORC + cell proportion change in CSF2RB-/-. (D) Modeling of GM-CSF in preventing ILC3 expansion and attenuating ILC3-related proinflammatory cytokines during intestinal injury. Our studies illuminate mechanisms of GM-CSF in perpetuating gut homeostasis through maintaining and regulating ILC3s. This novel aspect of regulating IBD pathogenesis through ILCs may lead to novel therapeutic targets.